Making Social Work More Socially Sustainable Through Participation: Rhetoric or Innovation? - Luca Pavani (SocietàMutamentoPolitica: Rivista Italiana di Sociologia)
This paper aims to explore the connection between social sustainability and participatory processes in the realm of social work, through a theoretical reflection. The guiding research questions for the work are: a) How can user participation enhance the social sustainability of social work? b)What should be the dynamic of participation between institutions and users to ensure the social sustainability of social work? In an effort to address these inquiries, we will initially conduct a comprehensive analysis of the current state of social sustainability literature to underscore the significance of user participation in social work. Subsequently, our focus will shift towards examining various forms and dynamics associated with user participation at the meso level of social work practice within the domain of welfare services in Italy. Our aim is to advocate for the adoption of co-creation processes, characterised by a bottom-linked dynamic, as an innovative approach with the potential to enhance the social sustainability of social work.